ANALISIS SISTEM PENGENDALIAN INTERNAL PADA SISTEM AKUNTANSI PEMERINTAH: STUDI KASUS PADA DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN LAMPUNG TIMUR - Okta Melinda Sari; Yulita Zanaria; Dimas Bagus Editya (Universitas Muhammadiyah Metro, 2023)
This study aims to find out how the Internal Control System in the Government Accounting System at the Department of Communication and Information, East Lampung Regency. The type of research used is qualitative with descriptive analysis method. Data collection techniques were carried out by means of observations and interviews conducted at government agencies, especially at the Communication and Information Office. Technical analysis using the PIECES analysis method to determine the effectiveness of the government accounting system is to use a compliance test. The results showed that the Government Internal Control System (SPIP) at the Department of Communication and Informatics of East Lampung Regency was running well, because its implementation was in accordance with the elements in the SPIP that had been determined based on PP no. 60 of 2008. The systems and procedures at the Communications and Informatics Service of East Lampung Regency are also quite adequate, supported by competent employees in their fields so that the error rate on control can be overcome. This results in the implementation of tasks not being fully efficient.